A MODEL OF AUTHENTIC TEACHING MATERIALS FOR GENERAL ENGLISH SUBJECT - Ryani Yulian; Yuniarti Yuniarti (STKIP Persada Khatulistiwa Sintang, 2020)
Designing teaching materials for General English at higher education has become a foundation of language teaching practices. The students at tertiary level should delineate the needs of the English language skill in the 21st century. This study aimed to conduct need analysis to create a model of teaching materials that can accommodate university students to improve English proficiency skill. This study focused on the realm of designing teaching materials based on authentic materials in the area of reading skill supplemented with listening skill. The initial need analysis investigated students' needs of reading text, the needs of multimodal texts, the problems in reading and listening skill. The study also invigoratedthe level of critical thinking for critical reading, and the perspectives of lecturer in General English class. A sample of 230 students at Management Program was selected to participate as the sample represented the nature of the homogenous language skill. The results of the study revealed that students prefer to get exposure on authentic materials with multimodal images. They need to read materials that can catalyze critical thinking skill in critical reading. Also, listening materials can serveas an additional material to enrich the reading materials on the basis of sources of authentic materials